In vitro susceptibility of Mycobacterium tuberculosis, Mycobacterium africanum, Mycobacterium bovis, Mycobacterium avium, Mycobacterium fortuitum, and Mycobacterium chelonae to ticarcillin in combination with clavulanic acid. - Casal, M J (1987)
The in vitro susceptibility of Mycobacterium tuberculosis, Mycobacterium bovis, Mycobacterium africanum, Mycobacterium avium, Mycobacterium fortuitum, and Mycobacterium chelonae (M. chelonei) to ticarcillin in combination with calvulanic acid (CA) was studied by the agar dilution method. All the M. tuberculosis, M. bovis, and M. africanum strains were inhibited at a ticarcillin concentration of 32 micrograms/ml or lower in combination with 5 micrograms of CA. M. chelonae and M. avium strains proved resistant to more than 128 micrograms of ticarcillin plus 5 micrograms of CA per ml. M. fortuitum strains needed 128 micrograms of ticarcillin plus 5 micrograms of CA to inhibit approximately 30% of the isolates.